Development of peptide inhibitors against dengue virus infection by in silico desigh and in vitro studies - Aussara Panya (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Dengue virus (DENV) infection is a global major concern with over 50 million reported cases a year. Presently, there are neither any approved vaccines nor effective drugs that are available; therefore, the development of anti-DENV drug is urgently needed. Several clinical reports revealed a positive association between the viremia and disease severity suggesting that the anti-DENV drug therapy can possibly ameliorates the disease severity as well as ending the transmission circuit to control the current outbreak situation. The surface envelope (E) protein of DENV is critical for the viral entry step which includes attachment and membrane fusion; thus, the blocking of envelope protein is an attractive strategy for anti-DENV drug development. This study aimed to search for novel peptide inhibitors to counter DENV infection through the targeting of E protein using a structure-based in silico design. Two selected strategies of inhibition included interference of membrane fusion process whereby the hydrophobic pocket on the E protein was the target, and the destabilization of virion structure organization through the disruption of the interaction between the envelope and membrane proteins, respectively. Following the first strategy, molecular docking technique was used to identify small peptides targeting the hydrophobic pocket. In the second strategy, the design of peptide inhibitor mimicking the ectodomain portion of membrane protein was performed to interfere with the protein-protein interaction. The designed peptides were tested for cytotoxicity to host cell, and its inhibitory effect on DENV foci formation in Vero cells. The peptide effects were further charaterized on the reduction of DENV genome, protein, and infectivity levels by using real-time PCR, cell-based flavivirus immunodetection and immunofluorence assay. Finally, the peptide inhibitory effect was tested with all four DENV serotypes (DENV1, DENV2, DENV3, and DENV4) in an effort to study the cross-serotype antiviral activity. Using a computer-aided design, peptide inhibitors targeting hydrophobic pocket revealed di-peptide inhibitor, Glu-Phe (EF), effectively inhibited DENV infection in cell culture system. Its most potential effect was observed for DENV2 with a half maximal inhibition concentration (IC50) of 96 ?gM, but it partially inhibited other serotypes. Treatment of EF at 200 ??M on infected cells also significantly reduced the viral genome and protein to 83.47% and 84.15%, respectively, corresponding to the reduction of infected cell numbers. An additional approach was carried out by using peptide mimicking membrane (M) protein, namely MLH40. Treatment of MLH40 caused the reduction of foci formation in four individual DENV serotype (DENV1-4) with IC50 of 24-31 ugM. Further charaterization suggested that the MLH40 specifically blocked viral attachment to host membrane, and treatment with 100 ?gM could diminish 80% of viral attachment. The inhibitory effect of MLH40 was observed in various target cell types including Vero, A549, and Huh7 cells at low-micromolar level. The molecular docking technique suggested that MLH40 interacting with envelope proteins can disrupt their regular dimer conformation. The binding of peptide to the target site was a key underlining the inhibitory effect. In summary, the designed peptide inhibitors targeting DENV E protein on hydrophobic pocket and M-binding site could inhibit the virus infection in a cell culture system. The results provide proofof- concept for the development of antiviral therapeutic peptide inhibitors to counter DENV infection through the use of a structure-based design targeting conserved viral protein.